2016
DOI: 10.1177/0269881116636107
|View full text |Cite
|
Sign up to set email alerts
|

BAP Position Statement: Off-label prescribing of psychotropic medication to children and adolescents

Abstract: The off-label use of medicines for children and adolescents remains a common and important issue for prescribing practice across child and adolescent psychiatry, paediatrics and primary care. This editorial focusses on psychotropic drug treatment, which plays an essential part in the comprehensive management of a range of child and adolescent psychiatric disorders. Despite a growing evidence base for drug treatment in child and adolescent psychiatric disorders, much psychotropic medication continues to be pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 10 publications
2
42
0
2
Order By: Relevance
“…Several antidepressants, antipsychotics, anti‐attention‐deficit/hyperactivity disorder (ADHD) medications and mood stabilizers indicated in adults have received regulatory approval for use in children and/or adolescents 5 , and many are used off‐label 6‐10 . However, despite evidence for the efficacy of a number of psychotropic medications in youth, the duration of untreated illness in depressive disorder 11 , bipolar disorder 12,13 , schizophre­nia 14 , obsessive‐compulsive disorder 15 , anxiety disorders 16 , and other mental disorders 17 is often long 18,19 , which adversely affects long‐term outcomes 14,20‐24 .…”
mentioning
confidence: 99%
“…Several antidepressants, antipsychotics, anti‐attention‐deficit/hyperactivity disorder (ADHD) medications and mood stabilizers indicated in adults have received regulatory approval for use in children and/or adolescents 5 , and many are used off‐label 6‐10 . However, despite evidence for the efficacy of a number of psychotropic medications in youth, the duration of untreated illness in depressive disorder 11 , bipolar disorder 12,13 , schizophre­nia 14 , obsessive‐compulsive disorder 15 , anxiety disorders 16 , and other mental disorders 17 is often long 18,19 , which adversely affects long‐term outcomes 14,20‐24 .…”
mentioning
confidence: 99%
“…[ 1 2 ] In principle, though it may not be compliant to the ethics in clinical practice, reports of off-label use of psychotropics have been widespread across clinical diagnoses and age groups. [ 1 3 4 5 6 7 8 9 10 11 ] Among all medications, psychotropics are one of the most commonly prescribed for off-label purpose. [ 5 12 ] A few studies from the Indian subcontinent had found that off-label use of psychotropics was seen in a significant proportion of prescriptions (up to 42%) and off-label uses were most common for indications (48.9%) followed by for dose (37.2%).…”
mentioning
confidence: 99%
“…More than one third of children with BD receive two or more medications belonging to different classes (i.e. mood stabilizers, antipsychotics, antidepressants or stimulants) feeding the problem of off-label prescriptions [63].…”
Section: Discussionmentioning
confidence: 99%